Natural Family Planning: Knowledge and Practices Assessment Among Couples In Its Utilization: A Study Carried Out In The Bamenda Health District, North West Cameroon - Elizabeth Nforlem, Akwanwi; Emmanuel Fonyuy, Bodzewan (International Research in Medical and Health Sciences, 2019)
People everywhere have developed various means of family planning methods in fertility regulation for reasons such as ensuring better maternal and infant health, paternal care for children, reducing the burden of poverty, improving standards of living, quality education. The rate of population growth worldwide has caused political leaders to encourage national and regional fertility regulation project as vital support for regulation of individual fertility have been evident in all cultures at all-time even in those societies in which social and religious rules have favored the abundant production of children.The main objective was to assess the knowledge and practice of natural family planning among couples in Bamenda Health District.The descriptive cross-sectional study design was used in which the investigator collected data from couples on their knowledge in the practice of NFP methods and their findings analyzed.A sample size of 50 couples was recruited for the study; 50 questionnaires were administered to them within the study period.A random sampling technique was used, where three catholic churches were selected in the Bamenda Health District. Questionnaires were administered systematically to couples who practice NFP in the reproductive age group in the various churches.Results show that the high level of awareness of NFP methods did not give a corresponding encouragement to couples in practicing NFP methods. Culture and religion played a major role in a couple’s decision to practice NFP methods and this is reflected in the husband’s domination in most decisions taking by couples in reproductive health issues. Furthermore, women are found to be more involved in the practice of NFP than men. Both husbands and wives decide on the choice of family planning to be used and comparing following the man and the woman, the man-made the major decisions (26%) as to (24%) for the woman. Also following the decision on child spacing, the woman made the major decisions (34%) as opposed to the man (22%). On the decision concerning the family size, the man-made the major decisions.